Induksi dan Proliferasi Embriogenesis Somatik In Vitro pada Lima Genotipe Kedelai - Saepudin, Adam; Khumaida, Nurul; Sopandie, Didy; Ardie, dan Sintho Wahyuning (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2016)
ABSTRACTSomatic embryo induction medium was reported to be genotype dependent for soybean. This study was aimed to obtain the optimum medium for embryo somatic induction and proliferation, and to regenerate somatic embryo of five soybean genotypes. Five soybean genotypes (Tanggamus, Anjasmoro, Yellow Biloxi, CG-22-10, and SP-10-4) were used in this study. The research was divided into four steps: (1) embryogenic callus induction of  five soybean genotypes, (2) embryogenic callus proliferation of five soybean genotypes, (3) optimation of embryo somatic induction on five soybean genotypes and (4) embryo somatic regeneration of five soybean genotypes. The induction experiment showed that based on number of embryogenic callus, the best somatic embryo-induction medium was 3% sucrose+ NAA 5 mg L-1+2,4-D 5 mg L-1+ Vitamin B5. Embryogenic callus number for each genotype tested was increased on proliferation media of 3% sukrosa + 2,4-D 5 mg L-1 + NAA 5 mg L-1+ Vit B5, and Yellow Biloxi gave the highest number of proliferated somatic embryos compared to other genotypes. Increasing number of globular somatic embryo of all genotypes was obtained from the optimation of somatic embryo induction media being used, and Tanggamus genotype gave the highest number of globular somatic embryo which followed by Yellow Biloxi genotype. Tanggamus and Yellow Biloxi genotypes were also successfully formed the four steps of somatic embryos (globular, heart, torpedo, and cotyledonary stages), but in regeneration medium of MS0 and media MS + sukrosa 10 g L-1 + GA3 2 mg L-1 + BAP 4 mg L-1 + Vit B5 only Tanggamus genotype was regenerated into plantlet.  Keywords: 2,4-D, NAA, somatic embryos, induction, proliferation